Therapeutic Alliance in Technology-Based Interventions for the Treatment of Depression: Systematic Review - Wehmann, Eileen (J Med Internet Res, 2020)
BACKGROUND: There is growing evidence that technology-based interventions (TBIs) are effective for the treatment of depression. As TBIs are gaining acceptance, a question arises whether good therapeutic alliance, considered a key aspect of psychotherapy, can be established without or with minimal face-to-face contact or rather changes if blended concepts are applied. While therapeutic alliance has been studied extensively in the context of face-to-face therapy, only few studies have reviewed evidence on alliance ratings in TBIs. OBJECTIVE: The purpose of this study was to examine therapeutic alliance in technology-based psychological interventions for the treatment of depression. METHODS: We searched Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, PsycINFO, PSYNDEX, CINAHL, clinical trial registers, and sources of grey literature for randomized controlled trials on TBIs in the treatment of adults with unipolar depression. All publications were selected according to prespecified criteria. Data were extracted by two independent reviewers. RESULTS: A total of eight out of 98 studies (9.5%) included in the review on TBIs for depression considered therapeutic alliance as part of their evaluation. The available data covered eight different treatment conditions, including four stand-alone treatments (face-to-face psychotherapy, email, telephone, and internet program) and four combined treatments (face-to-face psychotherapy plus a smartphone app and an internet program combined with face-to-face psychotherapy, treatment as usual, or email/telephone). On average, patients rated the alliance positively across all groups. Importantly, no relevant group differences regarding therapeutic alliance sum scores were found in any of the studies. Five studies investigated the relationship between patients’ alliance ratings and treatment outcome, revealing mixed results. CONCLUSIONS: Our results suggest that it is possible to establish a positive therapeutic alliance across a variety of different TBIs for depression, but this is based on a small number of studies. Future research needs to determine on what basis therapeutic alliance is formed in settings that do not allow for additional nonverbal cues, perhaps with adapted instruments to measure therapeutic alliance. TRIAL REGISTRATION: PROSPERO International Prospective Register of Systematic Reviews CRD42016050413; https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42016050413) INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): RR2-10.1136/bmjopen-2018-028042